Designing a tracked prime mover for in-field collection and transportation of oil palm fresh fruit bunches on low bearing capacity peat terrain - Ghassemi, Mohammad Hadi (2011)
A rubber tracked prime mover having 550 kg maximum payload has been successfully designed, developed, and evaluated to solve the vehicle floatation problems of in-field collection and transportation of the oil palm fresh fruit bunches (FFB) over low bearing capacity peat terrain in Malaysia. This tracked prime mover runs on a 37.7 kW (50.6 hp) @ 3600 rpm 4TNE84 Yanmar diesel engine driving in-tandem two units 50 cm^3/rev @ 350 bar. SAMHYDRAULIK variable displacement HCV 50 Series axial piston main pumps. Each of the pumps then runs a 565 cm^3/rev @ 250 bar SAi GM2 600 series high torque hydraulic motor to provide the rear sprocket torque for the 1800 mm ×350 mm metal reinforced rubber tracks. Vehicle engine power of 35.8 kW running at travel speed of 11 km/hr and sinkage limitation of 120 mm on low bearing capacity peat terrain of 19.50 kN/m^2 was selected based from the Uniform Ground Pressure Distribution (UGPD) and Non Uniform Ground Pressure Distribution (UGPD) straight motion mathematical models and turning motion model. Under a total vehicle of mass of 2500 kg, a total minimum driving torque of 2079 N.m was required at the rear track sprockets to overcome the tracks total motion resistance of 1.63 kN and develop the tracks tractive effort of 10.55 kN. Finally, computations were made to estimate the required hydrostatic pressure and flow for the driving motors of the rear sprockets to develop the expected tractive effort and the hydraulic cylinders on the dumping assembly on developed the expected tipping force. The field performance evaluation of the tracked prime mover regarding vehicle sinkage and speed was carried out on three type of terrain. Field evaluation of developed vehicle on asphalt under the engine speed from 1500 to 2500 rpm and total vehicle mass from 1950 to 2650 kg results with the travelling speed of 8.28 to 11.85 km/hr. Similarly under both engine speed and total vehicle mass variations, the vehicle travelling speed is 6.43 to 10.42 km/hr on tilled terrain. The vehicle average sinkage on low bearing capacity peat terrain at vehicle total mass of 2500 kg was found to be 104.2 mm which is 13.04% lower than the critical sinkage of 120 mm for the low bearing capacity peat terrain. The average sinkage range of the vehicle under total mass from 1950 to 2650 kg within 71.73 mm to 108.11 mm on tilled terrain and within 81.13 mm to 130.08 mm on the low bearing capacity peat terrain. The average sinkage of the right track is greater than that of left track by 20.52 % during left turning while the average sinkage of the left track is greater than that of right track by 15.93 % during right turning because of off set lateral location of center of gravity.